Forerunners of Coinage: Observations on the Monetary Forerunners of Coinage in the Aegean and the Near East with Special Reference to the Origins of Coinage. Ph. D. - Balmuth, Miriam S. (1964)
1964(?); Summary: Harvard Studies in Classical Philology 69 (Cambridge, Mass. 1965) 345-347; in Babylonia, coinage was of Persian introduction; in Mesopotamia, there was no native coinage until Hellenistic times.